Urban–sub-urban–rural variation in the supply and demand of emergency medical services - Li, Yue; Li, Ji; Geng, Jiayu; Liu, Tao; Liu, Xin; Fan, Haojun; Cao, Chunxia (Frontiers in Public Health, 2023)
Background: Emergency medical services (EMS) are a critical component of the health systems, often serving as the first point of contact for patients. Understanding EMS supply and demand is necessary to meet growing demand and improve service quality. Nevertheless, it remains unclear whether the EMS supply matches the demand after the 2016 health care reform in China. Our objective was to comprehensively investigate EMS supply-demand matching, particularly among urban versus suburban versus rural areas. Methods: Data were extracted from the Tianjin Medical Priority Dispatch System (2017-2021). From supply and demand perspectives, EMS resources and patient characteristics were analyzed. First, we performed a descriptive analysis of characteristics, used Moran’s I to explore the spatial layout, and used the Gini coefficient to evaluate the equity of EMS supply and demand. Second, we analyzed urban-suburban‒rural variation in the characteristics of EMS supply and demand by using the χ2 test. Finally, we examined the association between the EMS health resource density index and the number of patients by using the Spearman correlation and divided supply-demand matching types into four types. Results: In 2021, the numbers of medical emergency stations and ambulances were 1.602 and 3.270 per 100 000 population in Tianjin, respectively. There were gradients in the health resource density index of the number of emergency stations (0.260 vs. 0.059 vs. 0.036; P=0.000) in urban, suburban and rural areas. EMS demand was the highest in urban areas, followed by suburban and rural areas (24.671 vs. 15.081 vs. 3.210 per 1 000 population and pre year; P=0.000). The EMS supply basically met the demand in most districts (r=0.701, P=0.003). The high supply-high demand types with stationary demand trends were distributed in urban areas; the low supply-high demand types with significant demand growth trends were distributed in suburban areas; and the low supply-low demand types with the highest speed of demand growth were distributed in rural areas. Conclusion: EMS supply quantity and quality were promoted, and the supply basically met the demand after the 2016 health care reform in Tianjin. There was urban-suburban‒rural variation in EMS supply and demand patterns.